Perancangan Buku Cerita Pop-up Berbasis Karakter untuk Menanamkan Karakter Peduli Sosial Anak Usia Dini: Character-Based Pop-up Storybook Design to Instill Social Care Characters in Early Childhood - Nisa, Luthfatun; Wuryandani, Wuri (Pedagogia : Jurnal Pendidikan, 2018)
Social awareness (Caring) is one of the important character implanted in early childhood as the basic foundation for the development of other characters. Therefore, efforts to introduce are important. One of them is through storytelling activities by using media that appeal to children. This study aimed to acquire, collect, analyze information and data used as a reference in the design of an interesting storybook media that was pop-up based on character. Especially to instill the character of social caring in accordance with the needs of the field. This research method used field observation and also interview with Kindergarten teachers in Sewon Bantul Yogyakarta. Based on the results of observations and interviews found the results that children were more interested in the storybook with a more realistic appearance and can move the pop-up, but there was a little contens that telling about social caring. Therefore, with the desining of this media is expected to be a solution and facilitate the teachers to instill social caring character in early childhood then the childeren’s social caring can be developed well.